Associations between anthropometric indicators and both refraction and ocular biometrics in a cross-sectional study of Chinese schoolchildren. Issue 5 (10th May 2019) - Ye, Sheng; Liu, Shengxin; Li, Wenlei; Wang, Qifan; Xi, Wei; Zhang, Xin
Abstract : Objective: To identify associations between anthropometric indicators (height, weight and body mass index (BMI)) and both refraction and ocular biometrics in Chinese schoolchildren in Tianjin, China. Design: Cross-sectional study. Participants: A total of 482 (86.07%) students (6–15 years old) with no history of ocular or systemic pathologies were enrolled in this study. Methodology: Height and weight were measured using standardised protocols. Ocular biometrics (axial length (AL), vitreous chamber depth (VCD) and corneal curvature (CC)) were measured by a low-coherence optical reflectometry device. Cycloplegic refraction was measured using autorefraction. The AL/CC ratio and spherical equivalent refraction (SER) were calculated. Myopia was defined as SER ≤−0.50 dioptres (D). Multiple linear regression analysis was performed to explore the associations between anthropometric indicators (height, weight and BMI) and both refraction and ocular biometrics. Results: The overall prevalence of myopia was 71.16%. Overall, only height was associated with ALs, VCDs, AL/CC ratios and refractions after controlling for age, gender, parental myopia, family income, reading and writing distance and time spent outdoors. Furthermore, age-specific results demonstrated that height and weight were independently associated with refraction in participants aged 6–8 years and 9–11 years participants. Higher heights in schoolchildren were associated with longer ALs (regression coefficient b =+0.25 for each 10 cm difference in height, p<0.01), deeper VCDs ( b =+0.23, p<0.01), higher AL/CC ratios ( b =+0.04, p<0.01) and more negative refractions ( b =−0.48, p<0.01). Heavier weights were also associated with longer ALs (+0.29 mm, p<0.01), deeper VCDs (+0.29 mm, p<0.01), higher AL/CC ratios (+0.04, p<0.01) and more negative refractions (−0.48 D, p<0.01). Conclusions: Height and weight remained independently related to refraction and various ocular biometrics during the early adolescent growth period after adequately controlling for covariates, which could support the idea that a shared mechanism may regulate the coordinated growth of body and eye size in children.